PENGARUH CITRA MEREK DAN KEPERCAYAAN MEREK TERHADAP LOYALITAS KONSUMEN (STUDI KASUS PADA KORAN HARIAN PT. RIAU POS INTERMEDIA PEKANBARU) - Januar, Al Fajri; Karneli, Okta (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This study aims to determine the effect of brand image and brand trust on customer loyalty ( A case study on the daily newspaper PT . Riau Pos Intermedia Pekanbaru . The image of the brand as a variable ( X1 ) trust the brand as a variable ( X2 ) and customer loyalty as ( Y ) .               The method in this research is descriptive and quantitative using SPSS 20 , where the sample used is the consumer Pekanbaru Riau Pos daily newspaper with about 85 respondents consisted of five companies , 78 public and two government agencies . The formula used to determine the sample slovin , as well as a sampling technique by purposive sampling . Data collection through questionnaires . Results of analysis can be known that the brand image variable positive effect on customer loyalty , brand trust significant effect on consumer loyalty , and pengrauh significant between brand image and brand trust on customer loyalty .  Keywords : Brand Image, Brand Trust an Customer loyalty